2002
DOI: 10.3354/meps231115
|View full text |Cite
|
Sign up to set email alerts
|

Glycogen storage in the Riftia pachyptila trophosome: contribution of host and symbionts

Abstract: Glycogen storage in host tissue and symbiotic bacteria in the anterior trophosome of the vestimentiferan tubeworm Riftia pachyptila Jones, 1981, was investigated using transmission electron microscope and stereological methods. The relative glycogen content (RGC) of each partner was calculated from the percentage of host and bacterial cytoplasm area taken up by glycogen and from the percentage area that host and symbionts occupy within a trophosome lobule section. Our results show that host and symbionts contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 30 publications
3
17
0
Order By: Relevance
“…A 14C bicarbonate autoradiographic study showed that after 1-3 h of pulse incubations, the carbon incorporation rate of the central zone was almost as high as in the peripheral zone, but was lower in the median zone (Bright et al 2000). Glycogen distribution in the symbionts was not correlated with carbon incorporation (Sorgo et al 2002). These results provided evidence that the morphotypes differ physiologically in their rate of carbon fixation, incorporation, and storage.…”
mentioning
confidence: 73%
“…A 14C bicarbonate autoradiographic study showed that after 1-3 h of pulse incubations, the carbon incorporation rate of the central zone was almost as high as in the peripheral zone, but was lower in the median zone (Bright et al 2000). Glycogen distribution in the symbionts was not correlated with carbon incorporation (Sorgo et al 2002). These results provided evidence that the morphotypes differ physiologically in their rate of carbon fixation, incorporation, and storage.…”
mentioning
confidence: 73%
“…The released carbon is incorporated into fast-growing tissues and into the tube-secreting glands, as might be expected from the speed of tube secretion observed by Gaill et al (1997). The trophosome of Riftia contains much glycogen, both in the bacteria and the host cells (Sorgo et al, 2002). Before the trophosome of frenulates was known, glycogen was found to be abundant in the central core of the postannular trunk of the frenulate Siboglinum atlanticum (Southward, 1973).…”
Section: Trophosomementioning
confidence: 96%
“…Incorporation rates of organic carbon are high in the central zone where an increase in rods occurs and are also high in the peripheral zone in which biomass increases (Bright et al 2000). The concentration of glycogen, the organic carbon storage compound, is low in the central rods where division demands a high energy expenditure but is high in the large cocci where a surplus of organic carbon attributable to the lack of division allows for a greater glycogen pool (Sorgo et al 2002).…”
Section: Bacteriocyte Cell Cycle With Terminal Differentiationmentioning
confidence: 99%
“…Bacteria are either small and rod-shaped or round. The bacteria can be smaller than the host nuclei in the central region, similar to the median round symbionts, and smaller than the large round symbionts in the peripheral region of the trophosome (Sorgo et al 2002;Bright and Sorgo 2003). Because of the autofluorescence of the semithin sections, non-labeled host nuclei could be distinguished from symbionts and counted under the fluorescence microscope.…”
Section: Counting and Statisticsmentioning
confidence: 99%